Elementos para una teoría de la terminología: hacia un paradigma alternativo - Cabré Castellví, M.Teresa (Documenta Universitaria, 2026)
Semantic Scholar extracted view of "Elementos para una teoría de la terminología: hacia un paradigma alternativo" by M. Cabré
Keywords: Artigo; Terminoloxía

Fuentes de información terminológica para el traductor - Castellví, Mª Teresa (Hermēneus Revista De Traduccion E Interpretacion, 2009)
Hay que agradecer que Editorial Síntesis, en su colección de libros sobre "Biblioteconomía y Documentación", haya iniciado la publicación de una serie de obras que se ocupan, específicamente, de la Documentación aplicada a la traducción. La
Keywords: Capítulo; Terminoloxía

Un momento… (2026)

Bowker: Terminology and translation - Bowker (ter5, 2026)
Keywords: Capítulo; Terminoloxía

Crossref - Crossref (2026)
Choose from multiple link options via Crossref

Terminological Competence and Enhanced Knowledge Acquisition - LexiCon Research Group - Group, LexiCon Research (2026)
Faber, Pamela. 2003. Terminological Competence and Enhanced Knowledge Acquisition. Research in Language 1: 95-117.
Keywords: Capítulo; Terminoloxía

The use of translation technologies and generative artificial intelligence by terminology professionals in institutional settings: a case study - Wissik, Tanja (Tradumàtica tecnologies de la traducció, 2025)
Aquesta contribució explora l’ús de tecnologies de la traducció, incloses la traducció automàtica i la intel·ligència artificial generativa (GenAI), per part de professionals de la terminologia en entorns institucionals, a través de l’anàlisi de dades qualitatives procedents d’entrevistes realitzades en dues fases (entrevistes en línia sincròniques en la fase I i entrevistes asincròniques per correu electrònic en la fase II). L’estudi mostra que els professionals de la terminologia en entorns institucionals utilitzen una àmplia varietat d’eines per al treball terminològic. Gairebé tots han experimentat amb aplicacions de GenAI, però pocs han integrat plenament aquestes aplicacions al seu flux de treball fins ara. Tanmateix, s’analitzen l’impacte de les noves tecnologies en els fluxos de treball terminològic, com l’aparició del nou rol de gestor tecnològic i la necessitat d’adaptar els procediments de revisió i assegurament de la qualitat quan s’utilitza GenAI.
Keywords: Artigo; Terminoloxía

Polycentric Galician terminology. Notes on terminology planning: The Galician case - Galanes-Santos, Iolanda (Handbook of Terminology, 2025)
Abstract This chapter analyses the terminology planning in the language planning process that has been developing in Galicia over the last fifty years. In addition to a historical and sociolinguistic introduction, the normative framework of terminological development, terminological production ( Galanes 2003 , 2015 ), the role of institutions ( González 2015 , Gómez Clemente and Gómez Guinovart 2025 ) in the functions of terminological planning (research, standardisation, dissemination and implementation, evaluation, updating and training) ( Auger 1986 , Cabré 1999a , Bhreatnach 2011) are analysed. The main objective is to provide an overview of current Galician terminology and its planning.
Keywords: Capítulo; Terminoloxía

La competencia terminológica puntual en la traducción especializada: propuesta de definición y sistematización - Tebé, Carles (Cadernos de Tradução, 2024)
In the discipline of terminology, a distinction is made between different types of terminological competences, such as systematic terminology and ad-hoc terminology. The former is defined as the ability to create multilingual glossaries from specialized translations, and the ability to perform terminology management tasks applied to translation, incorporating corpus linguistics tools, performing terminology extraction, building terminology databases, and carrying out computer-assisted translation and machine translation tasks. Ad-hoc terminology is defined as the competence that a specialized translator should have in order to solve terminology problems that arise in a specialized translation. There is much less literature concerned with describing and systematizing this competence, and these approaches come from the field of terminology: Arnzt & Picht (1982), Célestin et al. (1984), Cabré (2004), Tebé & Pissolato (2019), Franco (2020). Translatology studies have traditionally paid little attention to ad-hoc terminology since they do not categorize terminological problems in translation as a singular entity that requires particular attention. This article presents a proposal for defining and systematizing the competences that a specialized translator should have when acting as an ad-hoc terminologist. The corpus of texts used to illustrate the competences consists of different scholarly articles in English in the field of biomedical sciences (review articles and experimental articles), translated into Spanish by different cohorts of a translation Master’s level students.
Keywords: Artigo; Terminoloxía

Aspectos terminológicos de los sistemas de traducción automática neuronal - Quiroz Herrera, Gabriel Ángel; Díaz Laínez, Giovanny (Traducción automática en contextos especializados, 2023)
Keywords: Capítulo; Terminoloxía

Panorama teòric de la terminologia actual (Theoretical overview of current terminology) - Castellví, Teresa Cabré; Casafont, Mercè Lorente (Terminàlia, 2021)
En aquest article es distingeix la noció de teoria integral o de paradigma en terminologia de la noció de model teòric de la lingüística adoptat per la terminologia. Dins de l’aproximació lingüística de la terminologia s’apliquen diversos models vinculats a la lingüística generativa, la lingüística funcional o la lingüística cognitiva, per a descriure i explicar fenòmens concrets de la terminologia. Algunes d’aquestes adopcions de models han estat anomenades inadequadament “teories”, cosa que distorsiona el panorama epistemològicde la terminologia.
Keywords: Artigo; Terminoloxía

La enseñanza de la terminología en el Grado de Traducción e Interpretación del sistema universitario español - Rodríguez Tapia, Sergio; Oliva Sanz, Carmen (Terminàlia, 2021)
Aquest treball pretén esbossar una panoràmica de la situació de la docència de la terminologia a Espanya. Per a aquest estudi s’han analitzat els objectius i resultats d’aprenentatge, la bibliografia i els continguts que apareixen a les guies docents de les assignatures relacionades amb la terminologia en les titulacions de Traducció i Interpretació de les universitats espanyoles. This paper seeks to present an overview of the situation in the field of terminology teaching in Spain. To conduct this study, we have analyzed the teaching objectives and learning outcomes, the bibliography, and the contents that appear in the teaching guides for the subjects relating to terminology in the Translation and Interpreting undergraduate studies of the Spanish universities. Este trabajo pretende esbozar una panorámica de la situación de la docencia de la terminología en España. Para este estudio se han analizado los objetivos y resultados de aprendizaje, la bibliografía y los contenidos que aparecen en las guías docentes de las asignaturas relacionadas con la terminología en las titulaciones de Traducción e Interpretación de las universidades españolas.
Keywords: Artigo; Terminoloxía

La competencia terminológica en la traducción especializada: definición y propuesta de medición en estudiantes de traducción*** - Toro, Javiera Vergara; Fernández-Silva, Sabela (Mutatis Mutandis. Revista Latinoamericana de Traducción, 2021)
La gestión terminológica es uno de los mayores desafíos de la traducción especializada, pues los términos condensan el conocimiento especializado y aseguran ...
Keywords: Artigo; Terminoloxía

La estación de trabajo del traductor en la era de la inteligencia artificial. Hacia la traducción asistida por conocimiento - Vargas-Sierra, Chelo (Pragmalingüística, 2020)
ICT development, together with innovations in artificial intelligence and machine learning, along with translation market needs, has led to significant and constant progress in translation technologies. The innovations that are emerging in this intelligent age where technologies learn automatically lead to a new generation of computer-assisted translation systems: knowledge-assisted translation (do Carmo et al., 2016: 149). We offer an analysis of the current tasks in each project process in a CAT and a knowledge environment. This paper begins with the concept of the translator's workstation and then details its different phases according to the standard that regulates translation service providers. We conclude with the central tasks that will be optimized by intelligent technologies, which will create a more knowledge-driven workflow.
Keywords: Artigo; Terminoloxía

EL DESARROLLO DE LA COMPETENCIA SOBRE VARIACIÓN TERMINOLÓGICA EN ESTUDIANTES DE TRADUCCIÓN E INTERPRETACIÓN:: UNA EXPERIENCIA DE COLABORACIÓN INTERUNIVERSITARIA. - Silva, Sabela Fernández (RLA. Revista de Lingüística Teórica y Aplicada, 2019)
La variación terminológica constituye un problema de traducción frecuente que se da a nivel intralingüístico, por la existencia de distintos términos para referirse al mismo concepto, como a nivel interlingüístico, por la existencia de distintos equivalentes de traducción para un mismo término. En este artículo se presenta una propuesta para desarrollar la competencia sobre variación terminológica en estudiantes de traducción e interpretación en el marco de un proyecto de colaboración entre universidades. El encargo consistió en documentar la base de datos VariMed, que contiene variantes denominativas de enfermedades en español e inglés, con las variantes empleadas en el español de Chile. Se planteó un escenario de enseñanza-aprendizaje colaborativo y situado, donde se simuló un entorno profesional basado en un encargo real. A través del trabajo los estudiantes aprendieron la metodología del trabajo terminológico puntual; y desarrollaron conocimiento teórico y práctico sobre la variación terminológica y su gestión en la traducción. Como resultado del trabajo, los estudiantes elaboraron 1.170 fichas, 360 con variantes no registradas en VariMed. La propuesta didáctica se evaluó mediante una encuesta y un informe autoevaluativo. Los estudiantes encontraron mayores dificultades en la compilación de un corpus médico del español chileno, la identificación de variantes terminológicas y la validación con expertos. Por otro lado, los estudiantes reconocieron la utilidad del trabajo para su formación como traductores/intérpretes y valoraron muy positivamente su carácter situado, especialmente la colaboración científica entre universidades.
Keywords: Artigo; Terminoloxía

La terminologie : un outil nécessaire pour le traducteur spécialisé - Navarro, Aura E. (Studia Romanica Posnaniensia, 2016)
Language disciplines, including Terminology and Specialized Translation, have made great strides after the second half of the twentieth century. This development, related to technological growth and international communication that occurred during this period, has resulted in a considerable increase of concepts. Thus, experts have become more and more aware of the importance of naming these new concepts. Specialized translators were among the first language professionals to recognize the need of mastering the terminology of specialized fields in order to perform their duties well (Antia et coll., 2005). In this work, we study the very close relationship between Terminology and Specialized Translation. We also study the theoretical and practical knowledge of Terminology that a specialized translator should have.
Keywords: Artigo; Terminoloxía

Terminografía galega e calidade: novos modelos - Galanes, Iolanda (Estudos de Lingüística Galega, 2015)
The production of terminology dictionaries including Galician as a working language has undergone significant development since 1980. Recent Galician terminographic work, generated within the linguistic normalization process, has been analyzed in publications in which this fact is related to language planning (e.g.Rodríguez Río 1996; Galanes 2003). Meanwhile, theoretical changes have occurred in terminology science, especially since Cabré 1999a, incorporating a social and communicative perspective into the treatment of terminological units. These innovations are being reflected in current applied work on terminology, especially with regard to how the relationship between terms and concepts is formulated (synonymy, polysemy, etc.), variation in terms and concepts, and the choice of sources of terminology, which are now corpus-based. The time has come for a re-evaluation of Galician terminography work in the light of these new developments, taking into account the new communicative perspective and aiming at interlingual mediation, with special attention to the quality of dictionaries. For this purpose, we have designed an evaluation system based on international indicators (Pointer 1995), communicatively oriented methods and the latest international standards (ISO) on terminographic work. The results findings of this study will affect the design of such workin the future.
Keywords: Artigo; Terminoloxía

La terminología como disciplina: aproximación interpretativa a su evolución epistemológica y metodológica a través de la caología - Zamorano Aguilar, Alfonso (Moenia: Revista lucense de lingüistica & literatura, 2013)
Keywords: Artigo; Terminoloxía

Situación de la Terminología española - De Irazazábal, Amelia Ramos (Institut Universitari de Lingüística Aplicada, 2010)
En aquest volum, que inclou les intervencions dels professors Jean-Claude Corbeil, Marcelo Diki-Kidiri i Luis Fernando Lara al seminari de terminologia de la I Escuela de Verano de Terminología organitzada per l'Institut Universitari de Lingüística Aplicada de la Universitat Pompeu Fabra, es parla clarament de les fal·làcies i inconsistències de la uniformització, que es presenta com un estadi natural de comportament, ja que ni la visió del món, ni tan sols la del món especialitzat, no és uniforme, ni les situacions sociopolítiques en les quals es desenvolupa el treball terminològic no són idèntiques. Aquesta diversitat suposa doncs que s'han d'adaptar les actuacions terminològiques a les circumstàncies pròpies de cada context, així com també seleccionar per a la terminologia la concepció teòrica més adequada a les actuacions.
Keywords: Capítulo; Terminoloxía

Terminological competence in translation - Montero Martínez, Silvia; Benítez, Pamela Faber (Terminology. International Journal of Theoretical and Applied Issues in Specialized Communication, 2009)
A Terminology course for Translation students must deal with the role of terminology in the translation process from both a theoretical and practical perspective. The objective of such a course is not to train translators as terminologists or documentation professionals, but rather as language mediators whose job is to facilitate interlinguistic communication. Translation students should thus learn how to carry out descriptive terminological work oriented towards producing a suitable target text. This means developing specific strategies as well as learning how to use available resources with a view to producing optimal translations. In this context, a truly effective Terminology course program must be adapted to fit new professional profiles. Such a program would target terminology management against the backdrop of specialized language translation. The specific characteristics of the translation process are what determine the type of terminological competence required.
Keywords: Artigo; Terminoloxía

Panorama intelectual de la terminología a través del análisis de redes sociales - Castro-Prieto, María Rosa; Olvera Lobo, María Dolores (Meta, 2008)
When transmitting scientific knowledge, authors weave a web of intellectual affinities through the works they cite that portrays trends and developments in research in their discipline. In the present article, we aim to establish an intellectual panorama of Terminology in which we depict the outstanding developments in research and the most influential authors. To do so, we analyze periodical publications that have appeared over a wide period of time. Author Citation Analysis (ACA) and the visual representation of the relationships between authors through social networks (specifically, pathfinder networks) is based on the premise that links are necessarily established between the authors cited in any specific work so that greater frequency of co-ocurrence indicates a stronger affinity between authors. Among other findings, our results show that the group of most frequently cited authors represents less than 1% of the total and that only 12% of authors have published three or more articles. Moreover, we can confirm that research in Terminology is developing in three clearly differentiated directions: theoretical foundations, Natural Language Processing and Socioterminology. , Lorsqu’ils transmettent des connaissances, les auteurs tissent souvent un réseau d’affinités intellectuelles par le biais des travaux qu’ils citent. Ce réseau offre un portrait des grands courants et de l’évolution de leur discipline. Le présent article a pour but de dresser un panorama du domaine de la terminologie en insistant sur ses développements et ses auteurs les plus influents. Pour ce faire, nous nous fondons sur les articles parus dans les périodiques du domaine, sur une période assez longue. L’analyse des citations et la représentation visuelle des relations entre les auteurs par le biais des réseaux sociaux postule que les citations établissent des liens entre les auteurs. Ainsi plus leur fréquence est élevée, plus les affinités entre ces auteurs seront fortes. Notre étude montre par ailleurs que le groupe des auteurs les plus cités représente moins de 1 % du nombre total et que seulement 12 % des auteurs ont publié trois articles ou plus. Enfin, cet article confirme que la terminologie, en tant que champ de recherche, se développe selon trois orientations bien distinctes : les fondements théoriques, le traitement des langues naturelles et la socioterminologie.
Keywords: Artigo; Terminoloxía

La terminologia : desenvolupament i utilitat en la formació de traductors - Cabré, M. Teresa (Tradumàtica: traducció i tecnologies de la informació i la comunicació, 2008)
This article proposes revising the evolution of Terminology as a discipline from the perspective of theory, as well as offering a description of the various current trends in theory. It establishes the difference between the theoretical aspects in the discipline and the methodological aspects which allow them to be put into practice in other disciplines such as translation. The conclusion offers convincing arguments concerning the relevance of terminology training for translators.
Keywords: Artigo; Terminoloxía

Terminologie et ontologie - Roche, Christophe (Langages, 2005)
AbstractOccidental philosophy has been for centuries implicated in the way languages refer to the world. Ontologies are the result of the thought applied to the existence of things. Nowadays, ontologies represent entities handled by companies, such as products, processes, and so on. They are more and more involved in data processing. Actually, one of the aims of ontology treatment is to make sure that a designation corresponds to a concept and that both –concept and designation– refer to a well specified object. Logic as science of well formulated propositions is also involved in such data modeling.
Keywords: Artigo; Terminoloxía

La terminología en la traducción especializada - Cabré, María Teresa (Manual de documentación y terminología para la traducción especializada, 2004)
Keywords: Capítulo; Terminoloxía

Fuentes de información en línea para la traducción especializada - García, Rosario Consuelo Gonzalo; Yebra, Valentín García (Arco/Libros, 2004)
Keywords: Capítulo; Terminoloxía

Análisis textual y terminología, factores de activación de la competencia cognitiva en la traducción - Martin, Anne (La traducción científico-técnica y la terminología en la sociedad de la información, 2002)
Keywords: Capítulo; Terminoloxía

Évaluation pédagogique de la recherche terminologique - Sader Feghali, Lina (Meta : journal des traducteurs / Meta: Translators' Journal, 2001)
Toute pratique pédagogique ne peut réussir sans mettre à l'épreuve les acquis des apprenants. Cette mise à l'épreuve requiert des instruments d'évaluation qui permettraient à l'enseignant, d'une part, de diagnostiquer les difficultés d'apprentissage et à l'apprenant, d'autre part, de comprendre ses erreurs et de les corriger. Cet article présente une stratégie d'évaluation suivie dans le cadre d'un cours d'initiation à la recherche documentaire et terminologique qui tente d'unir les deux approches sommative et formative pour aboutir à une évaluation objective des activités des apprenants.
Keywords: Artigo; Terminoloxía

La enseñanza de la terminología en España: problemas y propuestas - Cabré i Castellví, María Teresa (Hermeneus: Revista de la Facultad de Traducción e Interpretación de Soria, 2000)
El presente artículo analiza en detalle el estado de la enseñanza de la terminologñia en España. Para ello, se estudia las características y funciones de esta ciencia, los aciertos e insuficiencias de sus enfoques teóricos, y el estado de amplia diversidad actual el que se encuentra, antes de adentrarse en su enseñanza y en su alta rentabilidad para los traductores
Keywords: Artigo; Terminoloxía

El traductor y la terminología: necesidad y compromiso - Cabré, María Teresa (Panace@: Revista de Medicina, Lenguaje y Traducción, 2000)
Keywords: Artigo; Terminoloxía

Formar en terminología: una nueva experiencia docente - Cabré, Maria Teresa; Estopà, Rosa (Tradterm, 1997)
Neste trabalho, apresentamos a primeira parte de uma experiência docente que estamos desenvolvendo em diferentes cursos de formação destinados a estudantes com formação lingüística e sem conhecimento de outras áreas de especialidade. A inovação da experiência apóia-se basicamente em três pontos: em primeiro lugar, no fato de que se considera que o estudante será capaz de trabalhar em terminologia, aumentando, paralelamente, sua competência lingüística, cognitiva e funcional a partir da aquisição de habilidades; em segundo lugar, no fato de que se centra uma grande atenção no trabalho a ser realizado e se toma decisões durante o desenvolvimento do processo somente em função do trabalho definido; e, em terceiro lugar, na seleção de uma apresentação dos dados totalmente coerente com a definição do trabalho.No presente estudo, limitamo-nos a tratar das primeiras fases do trabalho terminológico, desde a apresentação do tema e a aquisição de conhecimento até a elaboração do fichário de pesquisa. Numa segunda parte, descreveremos a experiência com a elaboração do fichário terminológico (sua análise, revisão, apresentação e edição).
Keywords: Artigo; Terminoloxía; trabalho terminológico.

Terminologie et représentation des connaissances - Condamines, Anne (Didaskalia, 1994)
La terminología esté en el momento crucial de su histoha. El rencuentro con la inteligencia artificial de una parte, y, por otra parte las necesidades del incremento industrial en lo que concierne a la comunicación técnica, deberfa ayudarla a estructurar y organizar las futuras investigaciones en este dominio. Ellas deberian encontrar un terreno fértil en un acercamiento con la lingufstica, acercamiento que les permitirá encontrar un terreno de entendimiento con la inteligencia artificial. La terminología y la inteligencia artificial tienen en común el trabajar sobre la representación del conocimiento, la primera, via el estudio de los conceptos designados por los términos, la segunda, via el estudio de la formalización del conocimiento. El artfculo se propone mostrar cómo y por qué la colaboración es posible entre estas dos disciplinas.
Keywords: Artigo; Terminoloxía

Travail et vocabulaire spécialisés : prolégomènes à une socio-terminologie - Gambier, Yves (Meta : journal des traducteurs / Meta: Translators' Journal, 1991)
Un article de la revue Meta, diffusée par la plateforme Érudit.
Keywords: Artigo; Terminoloxía

Enseignement de la terminologie : une pratique pédagogique - Faribault, Marthe (Meta : journal des traducteurs / Meta: Translators' Journal, 1988)
Un article de la revue Meta, diffusée par la plateforme Érudit.
Keywords: Capítulo; Terminoloxía